2018
DOI: 10.14196/mjiri.32.119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating fear of hypoglycemia, pediatric parenting stress, and self-efficacy among parents of children with type 1 diabetes and their correlation with glycemic control

Abstract: Background: This study was designed to determine the level of fear of hypoglycemia (FoH), pediatric parenting stress and selfefficacy in parents of children with type 1 diabetes (T1D). Methods: In this cross-sectional study, 61 families of children with T1D who had been diagnosed for at least 6 months recruited from "Gabric Diabetes Education Association" in Tehran. Sixty mothers and 41 fathers of 61 children (26 girls, age: 6.0-12.7 years) were assessed using the Hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…During the course of our interviews, it emerged that worry, anxiety, and sorrow were closely linked to uncertainty of disease progression. This observation is consistent with prior studies that have shown parental caregivers of children with T1DM experience a heightened level of disease uncertainty compared to caregivers of other chronic disease states, which can exert adverse effects on the health and psychological condition of the parental caregivers and the children they care for 26 . Thus, medical staff should pay particular attention to these potential effects in parental caregivers.…”
Section: Reducing Persistent Psychological Strain In Parental Caregivsupporting
confidence: 92%
“…During the course of our interviews, it emerged that worry, anxiety, and sorrow were closely linked to uncertainty of disease progression. This observation is consistent with prior studies that have shown parental caregivers of children with T1DM experience a heightened level of disease uncertainty compared to caregivers of other chronic disease states, which can exert adverse effects on the health and psychological condition of the parental caregivers and the children they care for 26 . Thus, medical staff should pay particular attention to these potential effects in parental caregivers.…”
Section: Reducing Persistent Psychological Strain In Parental Caregivsupporting
confidence: 92%
“…This observation is consistent with prior studies that have shown parental caregivers of children with T1DM experience a heightened level of disease uncertainty compared with caregivers of other chronic states, which can exert adverse effects on the health and psychological condition of the parental caregivers and the children they care for. 26 Thus, medical staff should pay particular attention to these potential effects in early stages of the disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies did not report parents' age. 24,[27][28][29][30][31] Nine of the 12 studies focused their analyses on parents and caregivers alone (reporting only demographic and clinical data from children), [9][10][11][23][24][25][26]30,31 while three studies reported results from both parents and children. [27][28][29] The mean ± SD age of children ranged from 5 ± 2 to 15 ± 2 years.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The occurrence or frequency of hypoglycaemia was proxy-reported by parents in 10 studies, [9][10][11]23,[25][26][27][28]30,31 and was obtained via clinical records in two studies. 24,29 The recall periods for hypoglycaemia episodes varied across studies, with the most common recall period being episodes in the past 12 months in five studies.…”
Section: Definition and Measurement Of Hypoglycaemiamentioning
confidence: 99%
See 1 more Smart Citation